Fufang Duzhong Jiangu granule (FFDZ) ameliorates osteoarthritis development through maintaining subchondral bone homeostasis - Ling, Houfu; Xu, Jianbo; Zeng, Qinghe; Fang, Zhen; Cheng, Liangyan; Yuan, Wenhua; Chen, Jiali; Huang, Yuliang; Hu, Songfeng; Jin, Hongting; Tong, Peijian; Lu, Ke; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionOsteoarthritis (OA) is a widespread joint disorder predominantly marked by cartilage degeneration and the hardening of subchondral bone, with a lack of disease-modifying drugs for OA treatment. Fufang Duzhong Jiangu granule (FFDZ), a Chinese medicine, has demonstrated efficacy and safety in the clinical management of OA patients. However, the precise mechanisms through which it operates are still not fully understood.MethodsIn this study, we set out to explore the protective effects of FFDZ on destabilization of the medial meniscus (DMM) surgery-induced OA mice and elucidate its mechanism underlying the delay of OA progression both in vivo and in vitro. The pathological alterations of OA in DMM-induced mice were examined by gait analysis, μCT, histopathology and immunohistochemistry.ResultsWe observed that FFDZ administration effectively attenuated cartilage degradation and subchondral bone deterioration at 8 weeks after DMM operation. Gait analysis indicated that FFDZ could alleviate OA pain caused by surgery. Notably, FFDZ exhibited a potent inhibitory effect on osteoclast activity, as evidenced by tartrate-resistant acid phosphatase (Trap) staining, and repressed the osteoblastic expression of osterix and alkaline phosphatase (ALP) increasing after DMM operation in subchondral bone area. Subsequently, we confirmed that FFDZ reduced the number of CD44+ and CD73+ mesenchymal stem cells (MSCs) and inhibited the phosphorylation level of Smad2 (pSmad2) in subchondral bone. Similarly, FFDZ also suppressed the activation of TGF-β signaling in MSCs.DiscussionIn summary, this study demonstrated that FFDZ decelerated OA development in knee joints of mice after DMM potentially by maintaining subchondral bone homeostasis, providing evidences for the further application of FFDZ as an OA treatment.